Characterization of Cellulosic Fibers from the Inflorescences of Echinops sphaerocephalus: An Unexplored Source of Eco-Friendly Sustainable Fibers - Kawthar Z. Alzarieni; Abdel Rahman Bani Amer; Hilkka I. Kenttämaa (Journal of Natural Fibers)
This study identifies Echinops sphaerocephalus inflorescences as a novel, sustainable fiber source that avoids deforestation. Comprehensive characterization of their chemical, physical, thermal, and morphological properties reveals their potential for diverse applications. Chemical analysis shows that the fibers contain 39.5% cellulose, 36.5% hemicellulose, and 2.9% lignin, corroborated by FTIR spectroscopy. X-ray diffraction indicates a crystallite size of 2.25 nm and a crystallinity index of 47.5 ± 3.2%. Thermogravimetric analysis confirms the thermal stability up to 280°C. Morphological analysis by SEM reveals a hollow, microtubular structure with interconnected features and longitudinal microchannels, while AFM shows groove depths averaging 1.19 ± 0.49 μm. These structural traits contribute to a low density 0.51 ± 0.04 g/mL, tensile strength 34 ± 9 MPa, and thermal conductivity 0.049 ± 0.001 W/mK. A novel tea bag method, addressing a gap in assessing lightweight, hairy fibers, measured water absorption at 250 ± 33%. The combination of low density, high thermal stability, low thermal conductivity, and high water absorption positions these fibers as promising reinforcements for polymer composites, especially in biodegradable and lightweight applications. These findings highlight the untapped potential of this natural fiber for sustainable engineering and industrial uses. Such renewable fibers meet global demands for sustainable materials amid increasing environmental challenges.